Testing an innovative evaporative suppressant for reducing losses from lakes. Issue 3 (1st March 2014) - Sovocool, Kent; Morgan, Mitchell; Drinkwine, Michael; Sims, Daniel; Toussaint, Greg
Abstract : At a 28.5‐acre artificially created lake in Nevada, a short‐term trial of an evaporative suppressant decreased evaporative loss in comparative containers, but results for the lake application were inconclusive because of several confounding factors.